Transcriptomic Analysis Reveals Endometrial Dynamics in Normoweight and Overweight/Obese Polycystic Ovary Syndrome Women - Liu, Su; Hong, Ling; Lian, Ruochun; Xiao, Shan; Li, Yuye; Diao, Lianghui; Zeng, Yong (Frontiers in Genetics, 2022)
The aim of this work was to identify the transcriptomic characteristics of endometrium in normoweight and overweight/obese polycystic ovary syndrome (PCOS) potentially underlying the pathogenesis. This study included 38 patients undergoing in vitro fertilization: 22 women with PCOS and 16 matched controls. Each of the groups was subdivided into normoweight (body mass index (BMI) < 25 kg/m2) and overweight/obese (BMI ≥ 25 kg/m2) subgroups. Endometrium samples were collected in the secretory phase from controls or in a modeled secretory phase using daily administration of progesterone from women with PCOS before in vitro fertilization treatment. Transcriptome profiles were assessed by high through-put RNA sequencing to investigate distinct endometrial gene expression patterns in PCOS. Bioinformatic analyses revealed that endometrium from PCOS express significantly different transcripts encoding endometrial receptivity, inflammatory response, angiogenesis and energy metabolism. Additionally, our study demonstrated that the differentially expressed genes between normoweight and overweight/obese PCOS are involved in fatty acid metabolism, endometrial decidualization and immune response. For the first time, we have described the transcriptome characteristics of normoweight and overweight/obese PCOS endometrium. Our results indicate different endometrial gene expression between different subtypes of PCOS and non-PCOS women, which might affect endometrial functions in PCOS patients.